2018
DOI: 10.15406/ogij.2018.09.00312
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of disorders in obstetrics needing intensive care in a low resource setting

Abstract: SummaryBackground: Many disorders can occur during pregnancy, labour, postpartum. Some women become normal, some seriously ill and some die. It is essential to know disorders' burden.Objectives: of present study were to know burden of disorders, which cause severe illnesses, during pregnancy, birth, post birth, profile of such cases.Material Methods: Analysis of profile of cases admitted over 5 years at rural referral institute was done. Criteria was admission to intensive care area with system for ventilatory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
(14 reference statements)
0
1
0
Order By: Relevance
“…Taly et al 31 reported hemorrhage as the leading cause of severe illness. Simkhada et al 32 reported PPH responsible for 46% cases of mortality and morbidity, obstructed labor for 16% and eclampsia 14%.…”
Section: Discussionmentioning
confidence: 99%
“…Taly et al 31 reported hemorrhage as the leading cause of severe illness. Simkhada et al 32 reported PPH responsible for 46% cases of mortality and morbidity, obstructed labor for 16% and eclampsia 14%.…”
Section: Discussionmentioning
confidence: 99%